Record as strategic business / Arith Syakir Bunsu ... [et al.] - Bunsu, Arith Syakir; Daniel, Nur Zafika; Ramsa, Rizwanshah; -, Siti Nur Syazwanie; Empang Wan, Veronica (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Even while the majority of organizations can identify records, only a small percentage may be familiar with record management procedures. Record management is the systematic management of records and document data over their entire life cycle, starting at the point at which they are created by the originator. Then the stage is distributed, the information is made available, and it is accessible. After then, records can be accessed and used. The records must be kept by an authorised person throughout the maintain stage in order to be used in the future. When it comes to the dispose stage, the records must first be appraised before being delivered to an archive or records centre. There are three stages in a record's life cycle: active, semi-active, and inactive. The value of the record itself is represented by these stages. The evidence of every transaction is crucial in the business sector because failure risk can be reduced by reviewing the evidence of every transaction. The live records required for day-to-day operations in our company are dispersed, and I would assume that this is true for the majority of large businesses. Each departmental manager must decide how to proceed with the records, according to S.A. Tasker in 1958. The records should be monitored day by day because they are a record of every transaction, as demonstrated by the definition in the previous sentence. Lesley A. King, however, argued in 1997 that "good records management has a vital role to play in assuring the competitiveness, efficiency, and continuity of an organization's business, regardless of the domain or sector it happens to be in. Records are available in a variety of formats, including audiovisual and electronic as well as paper-based and other forms. However, it functions similarly to a record in protecting the accuracy of the data. The paper will explore record management and business system analysis. The significance of maintaining records as a strategic resource and record management professional training.